IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP PENATAAN SUNGAI BADUNG DALAM UPAYA PENGEMBANGAN PARIWISATA DI KOTA DENPASAR - I Gusti Ketut Purnaya; I Made Trisna Semara (Institut Pariwisata dan Bisnis Internasional, 2018)
The purpose of river toward humanâ€™s life is obvious since many history of humanity milestone explained in the river area. Nowadays, some rivers in Indonesia polluted because mostly waste issue, namely Badung River. Some efforts have been attempted by the government to arrange the surrounded area of Badung River. However, the result has not met the expectation since the solution still found its weakness and challenges. The aims of this research to understand the policy of Denpasar city and the implementation of Badung Riverâ€™s arrangement as an attraction in Denpasar city. Badung river arrangement and management determines environment conservation in building a sustainable development toward local community empowerment. Therefore, after the well management, government assumes the balance life or harmony in life is obtained based on its local genious. The methodology of this research is descriptive qualitative to describe social phenomenons. Collecting data utilize some methods such as observation, documentation and depth-interview with stakeholders. Pre-assumption of the community shows government policy regarding river arrangement has been well-managed, as it is seen from the policy implementation in arrangement in surround area of Badung River. Nevertheless, to optimize the Badung river development should begin from the change of human lifestyle in local community surround the Badung river area.Â Keywords: attraction, government policy, river